Diminished Systemic and Mycobacterial Antigen Specific Anti-microbial Peptide Responses in Low Body Mass Index–Latent Tuberculosis Co-morbidity - Rajamanickam, Anuradha; Munisankar, Saravanan; Dolla, Chandra Kumar; Babu, Subash (Frontiers in Cellular and Infection Microbiology, 2020)
Low body mass index (BMI) is a risk factor for progression from latent Mycobacterium tuberculosis infection to active tuberculosis (TB) disease. Anti-microbial peptides (AMPs) are multifunctional molecules that play a crucial role in the mammalian host innate defense mechanism. AMPs have been shown to have an important role in host immunity to TB infection. The association of antimicrobial peptides with low BMI–latent tuberculosis (LTBI) co-morbidity has not been explored. To study the association of AMPs with LTBI-BMI, we examined the systemic, baseline, and mycobacterial antigen stimulated levels of human neutrophil peptides 1–3, (HNP1-3), granulysin, human beta defensin–2 (HBD-2), and cathelicidin (LL-37) in individuals with LTBI and low BMI (LBMI) and compared them with individuals with LTBI and normal BMI (NBMI). LBMI was characterized by diminished systemic levels of HNP1-3, granulysin, HBD-2 and cathelicidin in comparison with NBMI. Similarly, LBMI was also characterized by diminished unstimulated levels of HNP1-3 and granulysin and diminished mycobacterial antigen stimulated levels of HNP1-3, granulysin, and HBD-2. In addition, certain AMPs exhibited a positive correlation with BMI. Our data, therefore, demonstrates that coexistent LBMI in LTBI is characterized by the diminished levels of HNP1-3, granulysin, HBD-2, and cathelicidin, thereby potentially increasing the risk of progression to active TB.